Pengaruh Shopping Lifestyle Dan Fashion Involvement Terhadap Keputusan Pembelian Impulsif Pada E-Commerce Tokopedia (Studi Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang) - Fahmi Faizal Izmy; Ronny Malavia Mardani; Nurhidayah Nurhidayah (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThe purpose of this study was to determine and analyze the effect of Shopping Lifestyle and Fashion Involvement on Impulsive Purchase DecisionsBy using a population of all students of the Faculty of Economics and Business, Islamic University of Malang), 96 respondents' answers were taken as the population. Using nonprobability sampling and using purposive sampling. Purposive sampling method uses a sampling technique with certain considerations by the researcherThe results in this study indicate that there is a partial influence of Shopping Lifestyle on purchasing decisions and the Fashion Involvement variable has no effect on purchasing decisions Keywords: Shopping Lifestyle, Fashion Involvement and Purchase Decision